2018
DOI: 10.1002/psp4.12363
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Dosing of Ganciclovir and Valganciclovir: How Model‐Based Simulations Can Prevent Underexposure and Potential Treatment Failure

Abstract: Intravenous ganciclovir and oral valganciclovir are effective in the prevention and treatment of pediatric cytomegalovirus ( CMV ) infection but various dosing regimens are used in medical practice. Population pharmacokinetic (PopPK) model‐based simulations were used to propose a new ganciclovir pediatric dosing algorithm for regulatory review and to evaluate the approved valganciclovir pediatric dosing algorithm against published dosing recommendations derived from quantitative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…It is well recognized that the most obvious difference between children and adults is the body size ( Holford et al, 2013 ), which is generally parameterized by WT or BSA. Our study demonstrated that WT as a primary covariate was superior to BSA when allometric exponent model was used, which was inconsistent with the Jorga et al (2019) . In addition, considering that GCV is a renally excreted antiviral drug with high hydrophilicity, the renal function would significantly alter the clearance capacity of GCV ( Tsai et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…It is well recognized that the most obvious difference between children and adults is the body size ( Holford et al, 2013 ), which is generally parameterized by WT or BSA. Our study demonstrated that WT as a primary covariate was superior to BSA when allometric exponent model was used, which was inconsistent with the Jorga et al (2019) . In addition, considering that GCV is a renally excreted antiviral drug with high hydrophilicity, the renal function would significantly alter the clearance capacity of GCV ( Tsai et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 80%
“…Currently, various dosing algorithms for intravenous ganciclovir have been proposed in published researches. And WT, BSA, eGFR or creatinine clearance values were used to compute individual GCV doses ( Jorga et al, 2019 ). According to the result of the covariate analysis, the WT-based algorithm was considered more appropriate than the BSA-based algorithm for dosage regimen design for critically ill pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 , whereas trough concentrations remained below the usual therapeutic threshold (e.g. < 0.5 µg/mL) [ 7 9 ] peak concentrations was high and AUC 0–12 h was close to 50 µg h/mL, which was within the therapeutic range (40–60 µg h/mL) suggested by some authors to treat CMV infection [ 10 , 11 ]. Eventually, viral load decreased quickly after 6 days at this dosage and became undetectable after 52 days.…”
Section: Case Presentationmentioning
confidence: 94%
“…It has a solubility of 3 mg/mL in water with pKa values of 2.2 and 9.4. Pediatric dosing in normal renal function ranges 20–40 mg/kg or 500–700 mg/m 2 every 8 h [ 113 , 114 ].…”
Section: The Next Wave Of Oral Liquid Formulation Development—formula...mentioning
confidence: 99%